2004
DOI: 10.1185/030079904125002964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic comparison of epoetin alfa and darbepoetin alfa

Abstract: These evaluations largely conclude that epoetin alfa is the better pharmacoeconomic value of the two currently available erythropoietic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 41 publications
2
15
0
2
Order By: Relevance
“…41 The frequency of dosing might not be related to a drug's half-life, however, because it might be possible that erythropoietin receptor cycle activation on erythroid precursors is more relevant than the terminal half-life. 42 All three erythropoetins have similar clinical efficacy. [43][44][45] Epoetin alfa and darbepoetin alfa are licensed for patients with solid tumors and nonmyeloid malignancies undergoing chemotherapy.…”
Section: Erythropoietinmentioning
confidence: 92%
“…41 The frequency of dosing might not be related to a drug's half-life, however, because it might be possible that erythropoietin receptor cycle activation on erythroid precursors is more relevant than the terminal half-life. 42 All three erythropoetins have similar clinical efficacy. [43][44][45] Epoetin alfa and darbepoetin alfa are licensed for patients with solid tumors and nonmyeloid malignancies undergoing chemotherapy.…”
Section: Erythropoietinmentioning
confidence: 92%
“…These show consistently that the key pharmacological differences between the erythropoietic proteins are the serum elimination half-life (t 1/2 ), the time taken to reach maximum serum concentration after subcutaneous (SC) administration (T max ) and reticulocyte response [36]. For example, in a study of 21 healthy male volunteers, in which the PK parameters of epoetin beta 100 IU/kg were compared with those of epoetin alfa 100 IU/kg [22], epoetin beta was associated with a significantly greater mean reticulocyte response (12% greater, p<0.05) and significantly delayed SC absorption (41.8% longer, p<0.05) compared with epoetin alfa.…”
Section: Pharmacokinetic Profiles Of the Erythropoietic Proteinsmentioning
confidence: 94%
“…A recent cost-minimisation analysis has attempted to compare the costs of epoetin alfa and darbepoetin alfa, by applying US average wholesale prices to dosage data derived from published clinical trials 20 . This analysis reported that epoetin alfa generally resulted in lower treatment costs than darbepoetin alfa.…”
Section: Key Cost Driversmentioning
confidence: 99%